Anti-IL17 therapies for psoriasis. (2nd January 2019) - Silfvast-Kaiser, Annika; Paek, So Yeon; Menter, Alan
ABSTRACT: Introduction : Interleukin-17 (IL-17) is a proinflammatory cytokine considered to play a significant role in the immunopathogenesis of plaque psoriasis. As a result, focus in clinical trials has undergone a shift towards disease specific targets, with the goals of more effective treatment and reduction in the incidence of serious adverse events. Areas covered : Two monoclonal antibodies targeting IL-17A (secukinumab, ixekizumab) and one against the IL-17 receptor (brodalumab) are approved for the treatment of moderate-to-severe plaque psoriasis. Herein, the clinical efficacy, safety and tolerability of each is reviewed by summarizing the existing literature (found via PubMed database). Expert commentary : The development and approval of the IL-17 inhibitor agents secukinumab, ixekizumab, and brodalumab has expanded psoriatic treatment with effective options, validating the importance of the pro-inflammatory role of IL-17 psoriatic pathophysiology. Biologic treatment options for psoriasis will continue to grow, especially IL-17 and IL-23 related agents, with an increasing specificity of agents to be available in the future.